Perspectives on Contemporary Legend.: International Society for Contemporary Legend Research, 26th International Conference, Dublin, Ireland, July 7 – 9, 2008. - Janeček, Petr (Lidé města, 2008)
Contemporary legends, rumors, gossip and other ephemeral forms of folk narratives typical for postmodern society represent one of the most interesting issues of contemporary social sciences. Since the 1980s, when these fictional narratives told as true were “discovered” by U.S. folklorists, their study attracted not only specialists in folk narratives, but also cultural anthropologists, sociologists, literary historians, media researchers and scholars from other disciplines. The vanguard of the study of these narratives has always been represented by the International Society for Contemporary Legend Research (ISCLR).